Pengaruh Kinerja Keuangan Bank Terhadap Rating Obligasi Bank Di Indonesia - Theofilus Steven Susanto; Bertha Silvia Sutejo; Deddy Marciano (Universitas Airlangga, 2012)
This research was conducted to provide empirical evidence about the effect of bank’s financial performance using CAMEL ratios (CAR, NPL, BMPK, BOPO, LDR), and SIZE as control variable toward bank’s bond rating in Indonesia from 2005 to 2009. The source of research data are financial reports obtained from Direktori Perbankan Indonesia and the source of bond rating data are obtained from official website of Pefindo. In data processing, researcher used ordered probit method analyzed using Eviews 4. From the research, it appeared that the capital adequacy and the size have positive effect toward bond rating. Asset quality, earnings, and liquidity have negative effect toward bond rating. There is no significant effect between management quality and bond rating. It can be concluded that the bond rating of banks in Indonesia from 2005 to 2009 influenced by capital adequacy, asset quality, earnings, liquidity, and size.